Single-cell profiling of CD11c+ B cells in atherosclerosis - Pattarabanjird, Tanyaporn; Srikakulapu, Prasad; Ransegnola, Brett; Marshall, Melissa A.; Ghosheh, Yanal; Gulati, Rishab; Durant, Chistopher; Drago, Fabrizio; Taylor, Angela M.; Ley, Klaus; McNamara, Coleen A. (Frontiers in Immunology, 2024)
Circulating CD11c+ B cells, a novel subset of activated B cells, have been linked to autoimmunity and shown to expand with age. Atherosclerosis is an age associated disease that involves innate and adaptive immune responses to modified self-antigens. Yet, the expression of CD11c on specific B cell subtypes and its link to atherosclerosis is poorly understood. In this study, we characterized the frequency of CD11c+ B cells in tissues in mice with aging. We observed an age-associated increase in CD11c+ B cells in spleen and bone marrow of ApoE -/-mice and this was associated with an increase in aortic plaque. In addition, we also utilized single cell multi-omics profiling of 60 human subjects undergoing advanced imaging for coronary artery disease (CAD) to subtype CD11c+ B cells and determine their frequency in subjects with high and low severity of CAD. Using unsupervised clustering, we identified 4 distinct clusters of CD11c+ B cells which include CD27 and IgD double negative 2 (DN2), age associated (ABC), CD11c+ unswitched memory (USWM), and activated Naïve (aNav) B cells. We observed an increase in frequency of both ABC B cells and DN2 B cells in patients with high CAD severity. Pathway analysis further demonstrated augmentation of autophagy, IFNg signaling, and TLR signaling in DN2 cells in high severity CAD patients. On the other hand, an increase in negative regulator of BCR signaling through CD72 was found in ABC cells in low severity CAD patients. Through investigating scRNAseq of atheroma, these DN2 cells were also found to infiltrate human coronary atheroma.